Bűn-e a vakság? Borbély Szilárd drámáiról - Miklós, Eszter Gerda (Studia Litteraria, 2016)
The dramatic texts of Szilárd Borbély, who was canonized as a poet and later as a prose writer, have been left beyond the vantage point of contemporary theatre. Zsuzsa Radnóti notices this distance when she refers to Borbély as a ”wait-listed author”, and a ”loss” for Hungarian theatre. Besides the examination of recent theatrical performances – most of which are based on prosaic works –, the paper attempts to highlight different approaches to Borbély’s plays and the legitimacy of the unique dramatic solutions of the texts by reading the dramatic oeuvre from the thematic opposition of seeing and blindness.